A Practical Guide to Implementing Population Newborn Screening (NBS) for Severe Combined Immunodeficiency (SCID) - H. Bobby Gaspar (MDPI AG, 2017)
This review should be seen as a practical tool, one which we hope illustrates potential routes to follow when seeking to implement or lobby for severe combined immunodeficiency newborn screening (SCID NBS) at a national or regional level. Experience has shown that there are country- and region-wide variations in terms of awareness of the need for SCID NBS and the processes required to demonstrate and prove the importance of SCID NBS. This guide therefore aims to share experiences and equip readers with evidence while also directing them to key further reading and resources that provide support, data, and existing frameworks that are relevant to making the case for mandatory NBS for SCID.